The Influence of Technological Knowledge, Pedagogy and Content on Ability Integrate Artificial Intelligence Moderated Gender - Fadilah Mutia Latifah; Muhammad Sabandi; Dini Octoria (Economic Education Analysis Journal, 2025)
This study examines the influence of technological knowledge, pedagogical knowledge and content knowledge on the ability to integrate artificial intelligence technology in high school economics teachers in Surakarta and to determine whether gender can moderate technological knowledge, pedagogical knowledge and content knowledge on the ability to integrate artificial intelligence technology in high school economics teachers in Surakarta. The population and sample of 68 were taken using total sampling, namely all high school economics teachers in Surakarta. Data collection using a questionnaire in the form of a google form. The validity test of the instrument used Confirmatory Factor Analysis (CFA) and the reliability test used Cronbach Alpha. Data analysis used hierarchical regression analysis and all data were processed using SPSS 26. The results of the study showed that technological knowledge, pedagogy and content partially had a positive and significant effect on the ability to integrate artificial intelligence technology in high school economics teachers in Surakarta and gender could moderate the relationship between technological knowledge and content with the ability to integrate artificial intelligence technology, but gender could not moderate the relationship between pedagogical knowledge with the ability to integrate artificial intelligence technology.